The Effect of Contact Time and Oil Palm Frond Activated Carbon Dose as an Adsorbent in Decreasing Iron (Fe) in Groundwater - Prasaningtyas, Asri; Febrianti, Nia; Azzahra, Rahmi; Ngang, Daniel Aprilianus (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Groundwater well is the alternative well providing water source in the city of Balikpapan, especially in its sub-district of Karang Joang, North Balikpapan, where the location has not been fully integrated with PDAM water pipes. Normally, the groundwater has minerals including iron (Fe). For the drinking water, the concentration standard of Fe follows the national law of Permenkes No. 493/Menkes/Per/IV/2010 which is 0,3 mg/L as the threshold. Oil palm frond is an organic matter that is found easily in East Kalimantan, containing high levels of lignin and cellulose which used to produce activated carbon. The activated carbon was evaluated with five variant doses of 5; 10; 15; 20; and 25 g/L over groundwater and the contact time of 30; 45; 60; 75; and 90 minutes. The time contact was measured by the rotation of the stirrer with the speed of 100 rpm. The results showed the optimum time contact of 30 minutes with the adsorbent dose of 5 g/L with the elimination efficiency of 99,56%. The time contact and the adsorbent dose variants have insignificant effect because of the least time contact as well as the least dose are the optimal condition in decreasing Fe